Hydrodynamics and simulation of air–water homogeneous bubble column under elevated pressure. Issue 10 (25th June 2019) - Tran, Bay V.; Nguyen, Dan D.; Ngo, Son I.; Lim, Young‐Il; Kim, Bongjun; Lee, Dong Hyun; Go, Kang‐Seok; Nho, Nam‐Sun
Abstract: A gas–liquid Eulerian computational fluid dynamics (CFD) model coupled with a population balance equation (PBE) was presented to investigate hydrodynamics of an air–water bubble column (1.8 m in height and 0.1 m in inner diameter) under elevated pressure in terms of pressure drop, gas holdup, mean bubble size, and bubble surface area. The CFD‐PBE model was modified with three pressure correction factors to predict both the total gas holdup and the mean bubble size in the homogeneous bubbly flow regime. The three correction factors were optimized compared to experimental data. Increasing the pressure led to increasing the density, reducing the bubble size, and increasing the gas holdup. The bubble size distribution moved toward a smaller bubble size, as the pressure increased. The modified CFD‐PBE model validated with experimental data and empirical models represented well hydrodynamics of the bubble column at P = 0.1, 1.5, and 3.5 MPa.